2019
DOI: 10.1021/acs.jafc.9b06247
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from Rosa roxburghii Tratt Fruit Attenuates Hyperglycemia and Hyperlipidemia and Regulates Colon Microbiota in Diabetic db/db Mice

Abstract: This study was aimed at investigating the hypoglycemic and hypolipidemic effects of a polysaccharide (RTFP) isolated from Rosa roxburghii Tratt fruit on type-2 diabetic db/db mice. The results indicated that the oral administration of RTFP could significantly decrease the body weight, fat, and liver hypertrophy and the levels of fasting blood glucose, serum insulin, and serum lipids of the db/db mice. Histopathological observation showed that RTFP could effectively protect the pancreas, liver, and epididymal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 66 publications
4
85
0
Order By: Relevance
“…HCD increased serum and hepatic lipid levels and the HSI, evidencing that high‐fat diet results in lipid accumulation in zebrafish. Supplementation with OGAG reduced the hepatosomatic index, a result in line with previous reports showing the beneficial effects of dietary treatment with natural polysaccharides in animal models of hyperlipidemia (Wang et al., 2020 ; Zhu et al., 2018 ). In addition, OGAG treatment improved serum and hepatic lipid parameters.…”
Section: Discussionsupporting
confidence: 90%
“…HCD increased serum and hepatic lipid levels and the HSI, evidencing that high‐fat diet results in lipid accumulation in zebrafish. Supplementation with OGAG reduced the hepatosomatic index, a result in line with previous reports showing the beneficial effects of dietary treatment with natural polysaccharides in animal models of hyperlipidemia (Wang et al., 2020 ; Zhu et al., 2018 ). In addition, OGAG treatment improved serum and hepatic lipid parameters.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Bifidobacterium , Lactobacillus , and Bacteroides are beneficial bacteria that can directly affect the immune system of the host, inducing intestinal immunity and enhancing immune function ( Yuan et al, 2018 ). Additionally, accumulating studies have demonstrated that the abundance levels of Ruminococcus , Parabacteroides , Dorea , Clostridiales , and Clostridium are increased, whereas those of Lactobacillales , Lactobacillaceae , Lactobacillus , Allobaculum , Bacteroides , Bifidobacterium , and Bifidobacteriaceae are decreased in diabetic animal models and patients ( Peng et al, 2014 ; Gil-Cardoso et al, 2016 ; Cui et al, 2019 ; Wang et al, 2019 ; Zhang et al, 2019 ; Li S. et al, 2020 ; Ma et al, 2020 ). In this study, pyridostigmine enhanced the abundance of Lactobacillales , Lactobacillaceae , Erysipelotrichaceae , Lactobacillus , and Allobaculum .…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on the conventionalization of germ-free (GF) and conventionally raised (CV) animals recognize the special role of the intestinal microbiota in host metabolism. Compared with healthy mice, diabetic db/db mice with lipid-metabolism disorder have lower levels of butyrate-producing bacteria (e.g., Fecalibacterium prausnitzii , Eubacterium rectale , and Roseburia intestinalis ) and higher levels of opportunistic pathogens (e.g., Clostridium hathewayi , Clostridium ramosum , and Eggerthella lenta ) ( Qin et al., 2012 ; Wang et al., 2020 ). The feces of rats with hyperlipidemia contains significantly more LPS-producing bacteria (e.g., Bilophila and Sutterella ) and mucosa-damaging bacteria ( Bilophila and Akkermansia muciniphila ) ( Song et al., 2017 ).…”
Section: Relationship Between Gut Microbiota and Hyperlipidemiamentioning
confidence: 99%